ENERGY POVERTY ALLEVIATION – A STEP FOR SUSTAINABLE ENERGY TRANSITION - Georgiev, Georgi Nikolov (Journal of Economic Development, Environment and People, 2022)
The paper investigates the issue of fuel poverty and its presence in the Bulgarian context. The focus of the analysis is on the potential for alleviation and – in the long term – elimination of energy poverty through the implementation of measures for energy efficient retrofit of residential multi-story apartment housing. An effective strategy tackling this topic at local scale is a key prerequisite for the achievement of the UN Sustainable Development Goals (SDGs) with particular relevance for SDG 7 Affordable and Clean Energy and SDG 11 Sustainable Cities and Communities. Achieving the optimal ratio of saved energy versus financial resources is the key to renovating housing at scale sustainably and efficiently. Energy poverty as a phenomenon is linked to the combined effect of three main factors - low household income, high energy costs and low energy efficiency of housing. There is a broad scientific consensus that this phenomenon has a serious negative impact on the quality of life and citizens’ health and wellbeing. Furthermore, energy poverty contributes to a huge waste of energy and also affects the physical dimension of the sustainable development of the built environment. Therefore, energy poverty exacerbates deficits and discrepancies for territorial economies and communities. Eliminating the problem of “fuel poverty” is often considered to be impossible without the support of the affected households through subsidies. Subsidies invested in energy-efficient housing reconstruction result in immediate savings in housing heating costs, which in turn leads to a tangible reduction in the “fuel poverty” experienced by residents of reconstructed housing. Energy efficient housing reconstruction (retrofit) is the fastest and most efficient (in terms of public resources) way to combat energy poverty. The financial resources required to enable these activities could also be obtained or complemented through financial engineering schemes with third party involvement.